Improving Student Online English Learning Engagement in Blended Learning Through Organization Development Interventions - Yuan, Aihong; Rucktum, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
The purpose of this study is to investigate how to improve student online English learning engagement through organization development interventions (ODIs) at Zhejiang Yuexiu University (ZYU). The current research was conducted with four research objectives: to discover the current situation of goal setting (GS), help seeking (HS), time management (TM), self-assessment (SA) and online learning engagement; to design and implement appropriate organization development interventions for improving GS, HS, TM, SA and promoting online English learning engagement; to identify the differences in GS, HS, TM, SA and online learning engagement between Pre-ODI and Post-ODI. This research investigated 42 students. The independent variables were goal setting, help seeking, time management and self-assessment, and the dependent variable was online learning engagement, including cognitive engagement, affective engagement and behavioral engagement. This research applied both quantitative and qualitative methods. The results of the paired samples t test and thematic analysis indicated that there was a significant difference in GS (t=9.58, p<0.01), HS (t=7.87, p<0.01), TM (t=8.91, p<0.01), SA (t=9.75, p<0.01) and online learning engagement (t=10.31, p<0.01) between pre-ODI and post-ODI. Based on the research findings, recommendations were proposed to improve goal setting, help seeking, time management and self-assessment